New Perspectives of the DaF-Reading Didactic: An Empirical Study about Inferential and Basic Grammar Strategies - Cosentino, Gianluca (Glottodidactica, 2014)
This paper focuses on the reading competence of a foreign language and aims at showing a particular approach to the reading comprehension of German texts. The role of inference and the knowledge of basic grammar while reading is discussed and particular analytical reading strategies are presented as a support to the theoretical questions. Their validity in the process of meaning reconstruction is finally approved by an empirical study.